Bank credit extension and real economic activity in South Africa : the impact of capital flow dynamics, bank regulation and selected macro-prudential tools /: the impact of capital flow dynamics, bank regulation and selected macro-prudential tools. ([2017]) - Gumata, Nombulelo; Ndou, Eliphas
No abstract available